PSYCHOLOGICAL FEATURES OF THE FORMATION OF LEARNING MOTIVES IN EARLY SCHOOL AGE IN THE CONTEXT OF DIGITAL TECHNOLOGIES IN MODERN EDUCATION (Universal International Scientific Journal, 2026)
This thesis analyzes the psychological characteristics of the formation of learning motives in primary school students in the context of the digitalization of modern education based on a systematic and comprehensive approach. The study scientifically substantiates the motivational and cognitive characteristics of the youth period, internal and external motivational factors, and the mechanisms of psychological influence of the digital educational environment. Based on the theoretical views of Uzbek psychologists and modern pedagogical approaches, effective conditions for the development of sustainable learning motives at the primary education stage are identified.
Keywords: learning motivation, early school age, intrinsic motivation, extrinsic motivation, digital learning environment, cognitive activity, psychological development, pedagogical innovation.